“Heterogeneity within Order” in Metal–Organic Frameworks - Furukawa, Hiroyasu; Müller, Ulrich; Yaghi, Omar M. (Angewandte Chemie (International ed.), 2015)
Metal–organic frameworks (MOFs) are constructed by linking inorganic units with organic linkers to make extended networks. Though more than 20 000 MOF structures have been reported most of these are ordered and largely composed of a limited number of different kinds building units, and very few have multiple different building units (heterogeneous). Although heterogeneity and multiplicity is a fundamental characteristic of biological systems, very few synthetic materials incorporate heterogeneity without losing crystalline order. Thus, the question arises: how do we introduce heterogeneity into MOFs without losing their ordered structure? This Review outlines strategies for varying the building units within both the backbone of the MOF and its pores to produce the heterogeneity that is sought after. The impact this heterogeneity imparts on the properties of a MOF is highlighted. We also provide an update on the MOF industry as part of this themed issue for the 150th anniversary of BASF. Mix and MOF: Most metal–organic frameworks (MOFs) are ordered and generally composed of only a few of repeating building unit. This Review is describes how the use of various different components in the MOF backbone and within the pores of the MOF can produce heterogeneity without losing the order (crystallinity) of the MOF structure.